Wandering as returning? Rethinking family dynamics of Chinese gay men under neo-familism through transnational mobility - Wang, Haohua (Frontiers in Psychology, 2025)
While extensive research has explored the causes of transnational mobility among Chinese gay men, there has been insufficient focus on the post-mobility challenges on how Chinese gay men reconcile with their family of origin. This study, grounded in Yan’s neo-familism framework, utilizes in-depth interviews with 20 Chinese gay men who have lived in the West for at least 1 year. It examines how transnational mobility enables these men to navigate their sexual identities in relation to their non-mobile parents. The findings indicate that transnational mobility alleviates family conflicts and facilitates the integration of gay identities into family structures through distinct reconciliation pathways fostering harmony and mutual understanding. This study significantly contributes to the field of sexual minorities in non-Western cultural contexts, particularly by illuminating the sophisticated family dynamics and reconciliation strategies that emerge in response to transnational mobility.